THE DEVELOPMENT OF TAHSIN, TAHFIDZ AND MUROJA'AH AL-QUR'AN (JUZ 30) IN ESTABLISHING MORALS AT MAN AMBON STUDENTS - Ahl Allah; Nur Khozin Khozin (IAIN Ambon, 2022)
Abstract: Every educational institution must have a vision, mission and purpose of building the educational institution, that is, the graduates are all outstanding and able to take part in society later. The most important provision of knowledge for students is the provision of the Qur'an. So the development of Tahsin, Tahfidz and Muroja'ah al-Qur'an became the initial capital taught by MAN Ambon for its students. The result of this coaching is that MAN Ambon students are able to memorize the Qur'an Juz 30 well and have an effect on the birth of noble morals in their better and better self.Keywords : Coaching Tahsin, Tahfidz and Muroja'ah